âSURABAYA UNDERGROUND AQUA PROJECTâ KONSEP PENGELOLAAN AIR MINUM, AIR LIMBAH, DAN AIR HUJAN PERKOTAAN DI BAWAH TANAH SEBAGAI SOLUSI PERMASALAHAN AIR DI KOTA BESAR - Nurdin, Fahmi Adha; Mulia, Gelora Jelang Takbira; Rosyidah, Badriyah; Ishar, Muhammad; Munir, Misbahul (Program Kreativitas Mahasiswa - Gagasan Tertulis, 2014)
Surabaya community faces serious water problems, such as drinking water, wastewater and rain water. Surabaya River has been polluted by domestic wastewater and does not meet the requirement as raw water of water treatment facility (PDAM). Otherwise, Surabaya does not have rain water utilization management system. This study is to determine a concept of Surabaya Underground Aqua Project that is a city-scale innovation of water management and technology. It is to create an idea of water recycle concept to obtain environmental sustainability. The concept includes networks planning and installation. Installation section is divided into two areas, namely area of wastewater treatment and rainwater and area of raw water treatment for drinking water. Furthermore, the piping networks are divided into two, namely drinking water supply systems and sewerage systems and rainwater collections system. The entire installations and networks are constructed underground building. From this idea, it obtains the concepts to improve the quality and quantity of drinking water supply in Surabaya. It also can overcome floods, preventing water crisis and can improve environmental health.Keywords: drinking water, rainwater, wastewater, water recycle